Epstein's inborn errors of development : the molecular basis of clinical disorders of morphogenesis - Erickson, Robert P., 1939-; Wynshaw-Boris, Anthony Joseph (Oxford monographs on medical genetics, 2016)
Epstein's Inborn Errors of Development provides essays on pathways of development and thoughtful reviews of dysmorphic syndromes for which the causative gene has been identified. It is a top-to-bottom revision of the landmark text that both revolutionized and accelerated the field of human genetics.